Convolution Product for Hilbert $C^*$-Module Valued Maps - Mawoussi Todjro; Yaogan Mensah (Sahand Communications in Mathematical Analysis, 2023)
In this paper, we introduce a convolution-type product for  strongly integrable Hilbert $C^*$-module valued maps on locally compact groups. We investigate various properties of this product related to uniform continuity, boundless, etc. For instance, we prove a convolution theorem. Also, we study the boundless of the  related convolution operator in various settings.